2013
DOI: 10.1080/14683857.2013.824666
|View full text |Cite
|
Sign up to set email alerts
|

Sticks, not carrots: immigration and rights in Greece and Turkey

Abstract: This piece critically examines migration policies in Greece and Turkey with an emphasis on the Greek experience. It examines four thematic areas which shape the migration debates: social change, citizenship, rights and sovereignty. It then turns to the case law of the European Court of Human Rights to assess the main challenges associated with migrants' rights: free trial, deprivation of liberty and conditions and procedures of detention and extradition. Honing in upon the case of Muslim migrants in Greece, it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Immigrants have been typically viewed as a vulnerable group that belongs to the lowest economic layers in Greece (Tsitselikis, ). They are also labeled as noncitizens and therefore have limited societal rights (Tsitselikis, ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Immigrants have been typically viewed as a vulnerable group that belongs to the lowest economic layers in Greece (Tsitselikis, ). They are also labeled as noncitizens and therefore have limited societal rights (Tsitselikis, ).…”
mentioning
confidence: 99%
“…Immigrants have been typically viewed as a vulnerable group that belongs to the lowest economic layers in Greece (Tsitselikis, ). They are also labeled as noncitizens and therefore have limited societal rights (Tsitselikis, ). People's attitudes toward immigrants are quite negative, with 61% of Greeks believing that immigrants do not enrich Greece culturally and 80% reporting that the presence of immigrants increases insecurity (Figgou, Sapountzis, Bozatzis, Gardikiotis, & Pantazis, ).…”
mentioning
confidence: 99%
“…In the process of nation-building and constructing a homogeneous national identity, minorities -such as the Turkish, Roma, Macedonian, and Jewish minorities -were assimilated or excluded (Just, 1989;Troumbetta, 2000). Membership in the EU and the incorporation of human rights regimes led to a greater recognition of cultural differences and minority rights (Tsitselikis, 2013). Legacies of intolerance and exclusion policies or attitudes towards migrants (Papataxiarchis, 2006;Ventoura, 2004) were tailored into public opinion and folklore, but in the last instance, according to my experiences, responded to popular demand.…”
Section: Neoliberal Hegemony Social Exclusion and Counter-hege-monic ...mentioning
confidence: 95%
“…A volatile institutional structure entails that the rules of the game pertaining to asylum and migration are subject to change. In Turkey and Greece, it was observed that sweep operations by the police could be followed by regularisation rounds; that border controls moved from one border region to the other and that seemingly random apprehension rounds on the street in Athens could lead to a detention period of a few hours, or even result in indefinite confinement (Wissink and Ulusoy, 2016;Tsitselikis, 2013).…”
Section: The Evolution Of Non-linear Migration Trajectoriesmentioning
confidence: 99%